-6(-2x+3)=

Simple and best practice solution for -6(-2x+3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(-2x+3)= equation:


Simplifying
-6(-2x + 3) = 0

Reorder the terms:
-6(3 + -2x) = 0
(3 * -6 + -2x * -6) = 0
(-18 + 12x) = 0

Solving
-18 + 12x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '18' to each side of the equation.
-18 + 18 + 12x = 0 + 18

Combine like terms: -18 + 18 = 0
0 + 12x = 0 + 18
12x = 0 + 18

Combine like terms: 0 + 18 = 18
12x = 18

Divide each side by '12'.
x = 1.5

Simplifying
x = 1.5

See similar equations:

| pi*2=3.18 | | x^3+5x^2-12x+6=(x-1)(ax^2+bx+c) | | -3x^2-21x+24= | | 5-4=30 | | 6x^3+5x^2-12x+6=(x-1)(ax^2+bx+c) | | 8(5x-4)= | | 0.09xX=95.41 | | 2/3=3x/20 | | 3x-15=(2x+10) | | 6x+10=6x | | 2.7x+13.758=4-2.97x | | 4-2m+4m+1= | | 8+5y=24 | | 4*x=2.5 | | (-x+9)*4= | | 7a-20=80 | | 3(2y+5)=30 | | 23x-5=25x-5 | | 2x+5=133 | | Y=58x+228 | | 7=5k-3 | | 5x-1=-5x+1 | | 7/2*63=7/2*2/7 | | M-5=11 | | (-x+7)*3= | | (g-7)(g+9)= | | 4v=8e-g | | 10m+3=38 | | 0.9=-log | | 2*-1=0 | | -2x^2-22x+24= | | 4v=8e |

Equations solver categories